Analysis of Legal Certainty Aspects in Indonesian Marriage Registration Rule - Imron Rosyadi; Aisyah Kahar (Jurnal Hukum dan Peradilan, 2023)
This paper examines the legal certainty aspects of marriage registration regulations in Indonesia. The controversy over whether or not a marriage is lawful without registration is still ongoing, depending on how Article 2 of Act No. 1/1974 regulating marriage is interpreted. The research method used in writing this paper is a literature study with normative legal research and descriptive analysis. Using the legal certainty aspect approach, the author analyzes various laws and regulations regarding marriage registration objectively. According to the findings of this study, the Marriage Act requires that every marriage be documented or registered by the marriage registration officer. However, Presidential Regulation (PERPRES) Number 96 of 2018 and Minister of Home Affairs Regulation (PERMENDAGRI) Number 9 of 2016 provide an alternative for those whose marriages have not been documented to create various population administrations by attaching a Statement of Absolute Responsibility (SPTJM). These two contradicting requirements have generated legal uncertainty in Indonesian marriage registration.